Avaliação dos ensaios de durabilidade do concreto armado a partir de estruturas duráveis - Jose Eduardo de Aguiar (2006)
In the contemporary world has been more and more observed the existence of reinforced concrete structures deteriorated by fast and intense degeneration processes, fact that induces the uncertainty of its safety and stability. Such situation, in many cases, is motivated by the lack of knowledge about the processes and degradation mechanisms, as well as for the absence of tests that appreciate, evaluate and esteem, the concrete durability adequately, once the control and evaluation requirements, adjusted or not, continue to be the amount of cement used in the concrete production and water/cement ratio. This investigation work intended to appraise the reliability and efficiency of the traditional tests used in the inspection and evaluation of the concrete durability in structures and constructions, in order to stipulate those that may be considered as the most appropriate or suitable, becoming, parameter and reference for analysis from this point on. The samples used in the experiments were extracted of old structures, considered as durable, selected among of the four classes of environmental aggressiveness foreseen in the ABNT specifications. Starting from the extracted specimens, some physical and mechanical concrete properties were appraised, as well as supplementary evaluations were made to provide the knowledge of concrete microstructure, to identify the presence of possible contaminants and, finally, to foresee the useful life of each one of the structures. Starting from a comparative study made among the structures, it was possible to infer that, the ultrasonic tests and absorption of water for capillarity showed to be the most efficient process in the analysis of the concrete durability. The present work shows a collection of pictures typifying the most observed pathologies of reinforced concrete deteriorated structures.